Development of art in Kosovo after World War II: The artist’s Art Works after the Second War and their similarities with the famous painters - Muharremi, Agnesa (Street Art & Urban Creativity, 2020)
At this article we wanted to present the Art Works of kosovo famous artists after World War II and their influences with famous artists from world.This study shows the liberation of the man under the Yugoslav regime at that time.There are few notes for our artists from Kosovo,our tradition , the creativity that was very deficient and it had been touched by social topics ,workers often suffered where the epic-historical legends and folklore sprout.Schools in Albanian were also lack and for that it was difficult for people who would spread the healthy figurative-visual culture,while in Europe was cultivated in great numbers.First of all we have mentioned Albanian Social Art and then we continued with Kosovo’s artists.